ANALISIS DAMPAK LISTRIK STATIS TERHADAP KERUGIAN PRODUKSI DAN BIAYA OPERASIONAL DI INDUSTRI - Ratri Rahmawati; Heni Risnawati; Tuti Nadhifah; Sigit Arrohman; Helmi Nur Fajri (Journal of Industrial Engineering & Technology Innovation, 2026)
One of the main issues with high-speed plastic cutting machines is the generation of static electricity due to friction between the plastic film and machine components during the production process. This study aims to analyze the impact of static electricity on production losses and operational costs in Cut-to-Length Rotary plastic cutting machines at PT Elsida Karya. The study focuses on the influence of static electricity on machine performance, production stability, and industrial operational efficiency. Previous studies have generally addressed product quality and machine maintenance, while research examining the relationship between static electricity and production losses and operational costs remains limited. The study employs a quantitative descriptive approach with a case study design. Data was collected through direct observation, interviews, production documentation, and analysis of operational data. The results indicate that static electricity causes plastic to adhere to the cutting blades, resulting in machine downtime of 15–40 minutes per shift and reducing production output from 3,000 pieces/hour to approximately 2,600–2,700 pieces/hour. Productivity decreased by approximately 10–13%, with estimated production losses reaching Rp9,000,000–Rp12,000,000 per month. The implementation of an anti-static system—including ionizers, optimized grounding, and anti-static brushes—is expected to improve production efficiency by 8–12%. Thus, a static electricity mitigation system is a critical solution for enhancing production stability and reducing operational losses in the plastics industry.